The Ethics of Technology Choice: Photovoice Methodology with Men Living in Low-Income Contexts. (June 2020) - Tarrant, Anna; Hughes, Kahryn
This article describes a two-phased reflexive ethical process initiated when choosing digital cameras for the photovoice method in research with men living in low-income contexts. While this participatory method aims to flatten power asymmetries in researcher–researched relationships, debate is needed about how pragmatic technology choices may inadvertently underscore or even reinforce participants' situated experiences of disempowerment and constraint. Critically engaging with an ethics of care approach to decision-making, we unpick what superficially appears to be a straightforward problem of method and demonstrate how pragmatic decisions may confound researchers' efforts towards democratisation in research. We reflect on how such efforts may inadvertently obscure contextual processes shaping the potential for participants to engage in research. Our reflections demonstrate the need to take seriously all decision-making throughout the research process as integral to a wider politics of method and ethics.